HUBUNGAN KEADILAN ORGANISASIONAL DAN KECURANGAN PEGAWAI DENGAN MODERATING KUALITAS PENGENDALIAN INTERNAL - Paramita Puspitadewi (STIE Perbanas Surabaya, 2012)
This study aims to test the moderating effect of internal quality control procedures on therelationship between perceptions of organizational justice and employee fraud. This researchalso aims to test the effects of five organizational factors, namely: environmental ethics, internalaudit activity, the risk management training, communication and information, andmonitoring on the quality of internal control procedures (ICP). This study was conductedusing the survey method of internal auditor of Universitas Surabaya, Universitas KristenPetra, Universitas Airlangga, STIE Perbanas Surabaya, and Universitas Widya Mandala.There were two developed models in this study. The first model test was using linier regressionanalysis and the second model was using residual test. The results showed that the firstmodel reveals that the environmental ethics affect the quality of internal control proceduresbut has a negative coefficient, internal audit activity and monitoring affect the quality of internalcontrol procedures but has a positive coefficient. And risk management training andcommunication and information not affect the quality of internal control procedures. In thesecond model suggests that reveals that the quality of ICP has a moderating effect on the relationshipbetween perceptions of organizational justice and employee fraud.